A Local Culture Development Strategy for Sonok Cattle with Quantitative Characterization of Cattle and Digital Market Development in Pamekasan, Madura - Bambang Kurnadi; selvia nurlaila; Badar Said; Dimas Bima widyabrata; Salman Alfarisi (UNIVERSITAS ISLAM LAMONGAN, 2025)
The Sonok cattle culture also supports the development of culture-based tourism while maintaining local values and social harmony, and can boost the local economy. One of the obstacles to the development of the Sonok cattle culture is that Sonok cattle breeding is still limited to certain areas in Madura, due to the limited market for Sonok cattle, which is still conventional in nature. This study aims to obtain clear data on the quantitative characteristics of Madura Sonok cattle and to improve the marketing of Madura Sonok cattle. To support the development of the local Sonok cattle culture and increase the marketing of Sonok cattle through digital markets. This research was conducted from July 2025 in the Sonok cattle breeding area in Pamekasan Regency, Madura. Research methods The methods used in this research were direct surveys at the contest site or at the homes of cattle owners, as well as interviews with Sonok cattle owners, judges, and Sonok cattle experts. Research Results Sonok cattle were divided into two age groups, namely 12-18 months and above 24 months, with the following results for body length, height, and chest circumference (cm): 124.82 ±4.28; 124.64 ± 3.14; 148.73 ±10.39 and 137.71 ±5.06; 137.26 ±4.74; 174.13 ±9.97. Meanwhile, the biggest obstacles and threats to the development of the Madura Sonok cattle breed in Pamekasan Regency are related to the limited availability of specialised capital and conventional trading venues (markets). The conclusion of this study is that the average body size of Sonok cattle exceeds the 2023 SNI standard, and marketing breakthroughs are needed through digital markets.